The best of G. Campbell Morgan - Morgan, G. Campbell (George Campbell), 1863-1945.; Turnbull, Ralph G. (Grand Rapids, Mich. : Baker Book House, 1992)
George Campbell Morgan (1863-1945) preached his first sermon at age twelve and without formal academic training became one of the most widely sought speakers of England and North America. Noted for his careful use of language and his thoughtful commentary, he wrote more than sixty books and pastored many churches. -- back cover
Christ and the bible -- Paul's estimate of life -- The hidden years -- But one thing -- Foundations -- To die is gain -- The spirit of the age -- The purifying hope -- The church evangelistic -- The unit of the church -- The dominion of man -- This darkness -- Disciples for building and battling -- The mediating ministry of the Holy Spirit -- The finality of the speech of God through the Son -- A man whose name was Job -- Yea, hath God said?
Formerly published under the title: A treasury of G. Campbell Morgan.
Includes bibliographical references (pages 226-229).
Keywords: Congregational churches -- Sermons